The Antibiofilm Nanosystems for Improved Infection Inhibition of Microbes in Skin - Yin-Ku Lin (MDPI AG, 2021)
Biofilm formation is an important virulence factor for the opportunistic microorganisms that elicit skin infections. The recalcitrant feature of biofilms and their antibiotic tolerance impose a great challenge on the use of conventional therapies. Most antibacterial agents have difficulty penetrating the matrix produced by a biofilm. One novel approach to address these concerns is to prevent or inhibit the formation of biofilms using nanoparticles. The advantages of using nanosystems for antibiofilm applications include high drug loading efficiency, sustained or prolonged drug release, increased drug stability, improved bioavailability, close contact with bacteria, and enhanced accumulation or targeting to biomasses. Topically applied nanoparticles can act as a strategy for enhancing antibiotic delivery into the skin. Various types of nanoparticles, including metal oxide nanoparticles, polymeric nanoparticles, liposomes, and lipid-based nanoparticles, have been employed for topical delivery to treat biofilm infections on the skin. Moreover, nanoparticles can be designed to combine with external stimuli to produce magnetic, photothermal, or photodynamic effects to ablate the biofilm matrix. This study focuses on advanced antibiofilm approaches based on nanomedicine for treating skin infections. We provide in-depth descriptions on how the nanoparticles could effectively eliminate biofilms and any pathogens inside them. We then describe cases of using nanoparticles for antibiofilm treatment of the skin. Most of the studies included in this review were supported by in vivo animal infection models. This article offers an overview of the benefits of nanosystems for treating biofilms grown on the skin.